Anal canal duplication with heterotopic gastric mucosa and anal stenosis: first case report and literature review - Liu, Chen; Xu, Chuanzhen; Xu, Xiaoliang; Zhang, Yan; Geng, Lei; Mei, Yanhui; Ji, Hong; Fu, Tingliang; Ding, Guojian (Frontiers in Pediatrics, 2024)
Introduction Anal canal duplication (ACD) is a rare entity of gastrointestinal duplication that may be asymptomatic or present complications, such as abscess, fistulae, or malignant changes. The diagnosis and rational management of ACD still need to be clarified. Case presentation We present a case of an 18-month-old girl with intractable perianal erosion and painful bowel movements for one year, and chronic constipation for six months. Fistulography revealed a tubular structure (3 cm in length), located posterior to the native anal canal. Mucosectomy was performed through a perineal approach combined with a coccigeal approach, and the postoperative course was uneventful. The pathological findings confirmed the diagnosis of ACD with heterotopic gastric mucosa, a rare combination that has not been described in the literature before. A literature search was conducted on the Medline database for studies reporting ACD in children. The study pool consisted of 77 cases of ACD from 32 studies, including the present case. According to our case report and in line with the literature, 43 cases (55.84%) were incidentally found; the most frequent symptom was constipation (14.29%), followed by painful anal mass or sacral pain (10.39%), and recurrent fistula (7.79%). Coexisting diseases were observed in 31 patients (40.26%), including 19 (24.68%) cases associated with presacral masses. Surgical management was employed in 73 patients (94.81%). ACD excision was performed in 47 patients (64.38%), combined with presacral mass resection or coccygectomy in 19 cases (26.03%). Conclusion Preoperative imaging, including fistulography, ultrasonography, and magnetic resonance imaging, can provide useful information, especially for screening its associated anomalies. To prevent potential complications, surgical removal of ACD and associated anomalies is recommended. Mucosectomy may be one of the most effective surgical options for ACD due to its excellent functional outcome.